A Feminist Menagerie. Issue 1 (April 2018) - Giraud, Eva; Hollin, Greg; Potts, Tracey; Forsyth, Isla
This paper appraises the role of critical-feminist figurations within the environmental humanities, focusing on the capacity of figures to produce situated environmental knowledges and pose site-specific ethical obligations. We turn to four environments—the home, the skies, the seas and the microscopic—to examine the work that various figures do in these contexts. We elucidate how diverse figures—ranging from companion animals to birds, undersea creatures and bugs—reflect productive traffic between longstanding concerns in feminist theory and the environmental humanities, and generate new insights related to situated knowledges, feminist care-ethics and the politics of everyday sensory encounters. We also argue, however, that certain figures have tested the limits of theoretical approaches which have emerged as the product of dialogue between feminist theory and environmental studies. In particular, we explore how particular figures have complicated ethical questions of how to intervene in broad environmental threats borne of anthropogenic activities, and of who or what to include in relational ethical frameworks.